KEPUTUSAN PEMBELIAN HP OPPO DITINJAU DARI KUALITAS PRODUK, INOVASI PRODUK, DAN BRAND IMAGE DI OPPO SERVICE CENTER - Diah Oktavianingrum; Djumali Djumali; Bambang Mursito (JURNAL ILMIAH EDUNOMIKA, 2020)
The implementation of a marketing strategy on target to be able to influence consumers makes a purchasing decision made by consumers. Consumer purchases in making decisions are influenced by reason and knowledge acquired. Companies must make the right strategy in order to influence consumers. The purpose of the research process is to determine and explain the quality of the product, product innovation and brand image of the results of consumer purchasing decisions in purchasing HP Oppo at Oppo Service Center. Research samples Sample accidental sampling of 100 consumers with the method used is multiple linear regression. The results of product quality research, product innovation and brand image simultaneously have a significant effect on the purchase decision of Hp Oppo at Oppo Service Center and in product quality, product innovation and brand image have a positive and significant effect on Hp Oppo purchasing decisions at Oppo Service Center. The purchase decision can be explained by three independent variables of 37.3% and the others are influenced by other variables. Keywords: product quality, product innovation, brand image, purchasing decisions